Peran Digitalisasi Dalam Meningkatkan Peran Perbankan Di Indonesia - Amalia Dwi Wahyuni; Putri Awaliah; Risma Aryani; Chaerul Sani (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research examines the role of digitalization in improving sharia banking services in Indonesia. Digitalization has become a major need in the banking industry, including the sharia sector, to increase efficiency, convenience and accessibility of services. Using a literature review and secondary data approach, this research analyzes the application of technology such as mobile banking, internet banking and sharia-based fintech. The study results show that digitalization can increase operational efficiency, customer satisfaction and financial inclusion, especially in areas that were previously difficult to reach. However, significant challenges such as low digital literacy, limited technological infrastructure, and data security threats still need to be overcome. This article provides strategic recommendations, including digital literacy education, investment in technology infrastructure, and strengthening data security, to optimize the potential for digitalization in sharia banking.